2020
DOI: 10.1002/adfm.202005245
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation of Intrinsically Disordered Protein Polymers Mechanically Stiffens Fibrin Clots

Abstract: Fibrin (Fb) networks self‐assemble through the coagulation cascade and serve as the structural foundation of blood clots. Following severe trauma or drug therapy, reduced integrity of Fb networks can lead to formation of clots with inadequate mechanical properties. A key feature of therapeutic interventions for hemostasis is therefore the ability to restore mechanical strength to clots formed under coagulopathic conditions. Here, an intrinsically disordered protein based on an elastin‐like polypeptide (ELP) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Extracellular deposits of proteins are ubiquitous. These include but are not limited to collagen, blood clot forming fibrin, insect elastic matrix protein resilin, hinge ligament of bivalve molluscs abductin, spider and insect silks, matrix proteins of squid suckers, attachment fibers and adhesives of mussels, and bacterial biofilms ( Muiznieks et al., 2018 ; Urosev et al., 2020 ; Seviour et al., 2020 ). Only two representative extracellular protein condensates, elastin and silk, will be briefly described.…”
Section: Biological Relevance Of Phase Separationmentioning
confidence: 99%
“…Extracellular deposits of proteins are ubiquitous. These include but are not limited to collagen, blood clot forming fibrin, insect elastic matrix protein resilin, hinge ligament of bivalve molluscs abductin, spider and insect silks, matrix proteins of squid suckers, attachment fibers and adhesives of mussels, and bacterial biofilms ( Muiznieks et al., 2018 ; Urosev et al., 2020 ; Seviour et al., 2020 ). Only two representative extracellular protein condensates, elastin and silk, will be briefly described.…”
Section: Biological Relevance Of Phase Separationmentioning
confidence: 99%
“…The large body of literature on biomedical applications has been regularly reviewed before, including recently by Varanko et al Here we only highlight a few examples of recent progress in the use of genetically engineered ELPs for medical applications. Urosev et al demonstrated a hemostatic-ELP protein variant by introducing charge and polar residues at the N- and C-termini. The ELP could be used to selectively bind to blood clots and modulate their physicochemical properties, such as improved resistance to enzymatic degradation and mechanical stability.…”
Section: Bioengineering Of Protein-based Materialsmentioning
confidence: 99%
“…These interactions took place through Gln- and Lys-residues on Fb γ-chains and α-chains, and AA cross-linked with hELP through its Gln- and Lys-blocks. 174 Hossain et al used intrinsically disordered peptide-polymers (IDPPs) for post-translational modifications (PTMs) adding a lipid chain to encode non-equilibrium phase behaviour transitions, an emergent frontier in biomacromolecular engineering. The IDR was based on a tropoelastin (Gly–X–Gly–Val–Pro) 80 domain (containing a mixture of Ala : Val 2 : 8 in the X position), while the lipids tested were a canonical PTM (M-IDPP) and an azide (–N 3 ) non-canonical PTM (ADA-IDPP).…”
Section: Applicationsmentioning
confidence: 99%